2017
DOI: 10.1103/physrevlett.119.067201
|View full text |Cite
|
Sign up to set email alerts
|

Raman Scattering from Higgs Mode Oscillations in the Two-Dimensional Antiferromagnet Ca2RuO4

Abstract: We present and analyze Raman spectra of the Mott insulator Ca_{2}RuO_{4}, whose quasi-two-dimensional antiferromagnetic order has been described as a condensate of low-lying spin-orbit excitons with angular momentum J_{eff}=1. In the A_{g} polarization geometry, the amplitude (Higgs) mode of the spin-orbit condensate is directly probed in the scalar channel, thus avoiding infrared-singular magnon contributions. In the B_{1g} geometry, we observe a single-magnon peak as well as two-magnon and two-Higgs excitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
81
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 28 publications
11
81
1
Order By: Relevance
“…Just as the β sector has an expected internal orbital structure, it was recently demonstrated by Raman spectroscopy that the low-energy α sector also consists of multiple excitations. In fact, a Raman study also revealed two excitations around 80 meV and associated them with two-Higgs and two-magnon scattering modes [8]. Although optical 80-100 meV phonon modes are not uncommon in transition metal oxides, the Raman study [8] suggests that our A-excitation is of magnetic origin.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Just as the β sector has an expected internal orbital structure, it was recently demonstrated by Raman spectroscopy that the low-energy α sector also consists of multiple excitations. In fact, a Raman study also revealed two excitations around 80 meV and associated them with two-Higgs and two-magnon scattering modes [8]. Although optical 80-100 meV phonon modes are not uncommon in transition metal oxides, the Raman study [8] suggests that our A-excitation is of magnetic origin.…”
mentioning
confidence: 79%
“…In fact, a Raman study also revealed two excitations around 80 meV and associated them with two-Higgs and two-magnon scattering modes [8]. Although optical 80-100 meV phonon modes are not uncommon in transition metal oxides, the Raman study [8] suggests that our A-excitation is of magnetic origin. To this end, we stress that our model spectra shown in Fig.…”
mentioning
confidence: 79%
“…Although CaFe 2 O 4 has shown no phonon anomaly near transition temperature, the anomalies close to the transition temperature are discussed in PrMnO 3 , NdMnO 3 , TbMnO 3 , and DyMnO 3 using polarized Raman spectroscopy and the phonon anomalies observed in BaFe 2 As 2 , which are attributed to spin–lattice electronic coupling. Polarized Raman measurements enabled observation of transient lattice disorder in very narrow temperature intervals at the onset of the multiferroic ordering in Eu (1‐x) Ho x MnO 3 and Higgs modes in the 2‐D antiferromagnet Ca 2 RuO 4 providing strong evidence for excitonic magnetism in it . Recently, polarization‐dependent micro‐Raman studies are shown to be useful for assignment of Raman modes even in polycrystalline ceramics …”
Section: Introductionmentioning
confidence: 99%
“…Originally discussed in the context of particle physics [2] and superconductivity [3], Higgs and Goldstone excitations were found in cold atom systems, such as superfluids [4][5][6][7][8] or supersolids [9]. Higgs and Goldstone modes are well-studied in superconductors today [10][11][12][13][14][15][16][17][18][19][20][21], and similar manifestations have recently been reported in charge density wave (CDW) systems [22][23][24], antiferromagnets [25][26][27], and excitonic insulators [28]. It has been debated whether the optical and acoustic vibrational modes of solids can be considered Higgs and Goldstone excitations of the crystal lattice [29].…”
mentioning
confidence: 96%